EFFECT OF ADDING ORGANIC ADDITIVE TO RON 92 FUEL ON ENGINE PERFORMANCE (Universitas Pendidikan Indonesia, 2025)
The increasing number of motorized vehicles in Indonesia has an impact on the increasing use of fuel oil. This will also have an impact on the depletion of the availability of petroleum reserves. Efforts are needed to save the use of fuel oil, one way is to improve engine performance by adding organic additives to fuel oil which are claimed to be able to improve engine performance consisting of engine power and torque values. However, these claims raise doubts as to whether these organic additives are beneficial to the vehicle. Based on the claims and doubts that arise, research is needed to determine the extent of the effect. This research was carried out with experimental tests using dynotest tools to find the value of engine power and torque where motorized vehicles were tested under conditions without additional organic additives and with additional organic additives. The results of the study, the addition of organic additives to engine power has an influence with an increase between 1.52% to 2.24% and for engine torque has an influence with an increase between 1.71% to 3.2%. Based on these findings, the claim of organic additives to improve engine performance is true. Peningkatan jumlah kendaraan bermotor di Indonesia berdampak kepada meningkatnya penggunaan bahan bakar minyak. Hal tersebut akan berdampak juga kepada menipisnya ketersediaan cadangan minyak bumi. Diperlukan upaya penghematan penggunaan bahan bakar minyak, salah satu caranya yaitu meningkatkan performa engine dengan menambahkan zat aditif organik pada bahan bakar minyak yang diklaim mampu meningkatkan performa engine yang terdiri dari nilai daya dan torsi engine. Namun, klaim tersebut menimbulkan keraguan apakah zat aditif organik tersebut bermanfaat pada kendaraan. Berdasarkan klaim dan keraguan yang timbul, diperlukan penelitian untuk mengetahui sejauh mana pengaruhnya. Penelitian ini dilaksanakan dengan uji eksperimental dengan menggunakan alat dynotest untuk mencari nilai daya dan torsi engine dimana kendaraan bermotor diuji dengan kondisi dalam keadaan tanpa tambahan zat aditif organik dan dengan tambahan zat aditif organik. Hasil penelitian tersebut, penambahan zat aditif organik terhadap daya engine memiliki pengaruh dengan peningkatan antara 1,52% sampai 2,24% dan untuk torsi engine memiliki pengaruh dengan peningkatan antara 1,71% sampai 3,2%. Berdasarkan temuan tersebut, maka klaim zat aditif organik untuk meningkatkan performa engine itu benar.